Behavioral Abnormalities in Knockout and Humanized Tau Mice - Gonçalves, Rafaella Araujo; Wijesekara, Nadeeja; Fraser, Paul E.; De Felice, Fernanda G. (Frontiers in Endocrinology, 2020)
Microtubule-associated protein tau assists in stabilizing microtubules and has been particularly implicated in Alzheimer's disease (AD). Given the importance of tau to AD pathogenesis and therapies, it is important to understand non-classic physiological functions for this protein inside and outside the central nervous system (CNS). Our group has previously shown that tau ablation triggers glucose intolerance and pancreatic dysfunction in mice, suggesting that tau plays a role in peripheral metabolic regulation. Little is known about the role of tau in anxiety. Moreover, inconsistent results have been generated regarding the effects of tau deletion in memory. Here, we characterize systemic insulin resistance, anxiety-related behavior and memory in 15 to 20 weeks old Wild-Type (WT), Tau knockout (TauKO) and a distinct hTau mouse model consisting of tau knockout expressing the longest isoform (2N4R) of a non-mutant WT human Tau protein under the prion promoter (hTau). Our findings demonstrate that tau deletion leads to anxiety-related behavior, impaired contextual and cued fear memory. The presence of a human Tau transgene did not ameliorate the phenotypes observed in animals lacking the mouse tau protein and it elicited impairments in learning, memory, and peripheral insulin sensitivity. Our results suggest that tau protein plays a role in memory and anxiety-related behavior. Our findings also indicate that previously unrecognized functions for tau protein may be a complicating factor in using animal models on the TauKO background. Understanding the link between tau pathophysiology and cognitive and metabolic alterations is of great importance to establish the complete contribution of tau protein to AD pathogenesis.